Web information system for the study of oral health - Melo, José (2021)
The human oral cavity is a complex ecosystem where multiple interactions occur and whose comprehension is critical to understand several disease mechanisms. In order to comprehend the composition of the oral cavity at a molecular level, it is needed to compile and integrate the biological information resulting from specific techniques, especially from proteomic studies of saliva. The objective for this work was to compile and curate a specific group of proteins related to the oral cavity, providing a tool to conduct further studies over the salivary proteome. Despite previous efforts to identify the protein components of saliva in healthy individuals and in several oral and systemic disorders, a resource compiling and reviewing all of these proteins is still lacking. In this paper we present a platform that integrates in a single endpoint all available information for proteins associated with the oral cavity. The proposed tool allows researchers in the biomedical sciences to explore organisms, proteins and diseases, constituting a unique tool to analyse meaningful interactions for oral health.